The effectiveness of the ice cream sticks strategy in the acquisition of psychological and philosophical concepts among female fifth-grade literary students in the subject of philosophy and psychology - Dr. Hawraa abdulrazaq hameed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
T This research aimed to identify the effectiveness of using (ice cream stick) strategy on concept acquisition in philosophy and psychology for fifth grade literary students and the using of experimental curriculum) experimental design with partial adjustment) (which contain two group experimental and post-test control) and the experiment was applied on random sample consisting of (80) sample from fourth grade literary students. The researcher conducts a parity process between two groups depended on the age of students in months and the general concept acquisition for all subjects at the first and second course in philosophy and psychology. This experiment was include (40) student in the experimental and (40) students in control group and all research standards were selected which includes selecting a study subject and behavioral purposes and daily teaching plans and select an achievement test which include (48) questions in the form of multiple choice question which contain four answers. Face validity and content validity for this test have been found and coefficient of difficulty and discriminatory power and reliability factors and T-test for two separated sample was used to show the results. Which amplify that there is a statistical difference for the experimental group which has been studied with this strategy. This show the effectiveness of this strategy in improving the acquisition for the fifth-grade literary students in philosophy and psychology this study give some of recommendations and suggestions.